DPP9 as a Potential Novel Mediator in Gastrointestinal Virus Infection - Ángela del Castillo-Izquierdo; José María Moreno-Navarrete; Jessica Latorre; María Arnoriaga-Rodríguez; Marta Ballanti; Giovanni Monteleone; Omero Alessandro Paoluzi; Geltrude Mingrone; Josep Puig; Rafael Ramos; Josep Garre-Olmo; Mariona Jové; et al. (MDPI AG, 2022)
Dipeptidyl peptidase 9 (DPP9) is a member of the dipeptidyl peptidase IV family. Inhibition of DPP9 has recently been shown to activate the nucleotide-binding domain leucine-rich repeat 1 (NLRP1) inflammasome. NLRP1 is known to bind nucleic acids with high affinity and directly interact with double stranded RNA, which plays a key role in viral replication. DPP9 has also recently emerged as a key gene related to lung-inflammation in critical SARS-CoV-2 infection. Importantly, DPP9 activity is strongly dependent on the oxidative status. Here, we explored the potential role of DPP9 in the gastrointestinal tract. We performed transcriptomics analyses of colon (microarray, n = 37) and jejunal (RNA sequencing, n = 31) biopsies from two independent cohorts as well as plasma metabolomics analyses in two independent cohorts (n = 37 and n = 795). The expression of DPP9 in the jejunum, colon, and blood was significantly associated with circulating biomarkers of oxidative stress (uric acid, bilirubin). It was also associated positively with the expression of transcription factors (NRF-2) and genes (SOD, CAT, GPX) encoding for antioxidant enzymes, but negatively with that of genes (XDH, NOX) and transcription factors (NF-KB) involved in ROS-generating enzymes. Gene co-expression patterns associated with DPP9 identified several genes participating in antiviral pathways in both tissues. Notably, DPP9 expression in the colon and plasma was strongly positively associated with several circulating nucleotide catabolites (hypoxanthine, uric acid, 3-ureidopropionic acid) with important roles in the generation of ROS and viral infection, as well as other metabolites related to oxidative stress (Resolvin D1, glutamate-containing dipeptides). Gene-drug enrichment analyses identified artenimol, puromycin, anisomycin, 3-phenyllactic acid, and linezolid as the most promising drugs targeting these DPP9-associated genes. We have identified a novel potential pathogenic mechanism of viral infection in the digestive tract and promising existing drugs that can be repositioned against viral infection.